Comparison of Phenolic Contents and Antioxidant Activities for Black and White Desert Truffles Spread in Syria - Al-Atassi, Abdullah Zuhair; AL-KHATIB, Racha Aboualkher; OTHMAN, Mohammad Abdulraouf (Iraqi Journal of Pharmaceutical Sciences, 2022)
Desert truffle is considered as a type of Syrian wild fungi that spreads heavily, and it occupies important rank in folk medicine, where its aqueous extract is used for the treatment of some eye and skin illnesses, and people prefer the use of black truffle. This work interested in studying of the most available species; Terfezia claveryi (black) and Tirmania pinoyi (white). The extracts of the two species of truffle were prepared by maceration with water, methanol, and ethanol 70%. Their total phenolic contents (TPC) and total flavonoid contents (TFC) were analyzed using Folin-ciocalteu and Aluminum chloride methods respectively, and their antioxidant activities was tested using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Ferric Reducing Antioxidant Power (FRAP) methods, after microscopic examination and detection of phytochemical components. Then, phenolic profile of ethanolic 70% extract of black truffle T.claveryi was studied by using LC-MS/MS. The values of TPC were between 25.3-43.6 mg GAE/g dry extract and TFC were between 2.5-6.8 mg QE/g dry extract. The values of DPPH (IC50) and FRAP were between 5.6-9.0 mg/ml and 90.1-153.4 µmol AAE/g dry extract respectively. There is a great similarity in content and activity of two species, also the aqueous extract is similar to other extracts in content and activity, and this means that the method of extract preparation in traditional medicine is reliable. It has been predicted about 14 phenolic compounds in the extract; as p-Hydroxy benzoic acid, Syringic acid and trans-Cinnamic acid. As a result, both truffle species are a new rich resource of antioxidant compounds which are usable in nutritional, cosmetic, and therapeutic applications.